Out of Place Artists, Pedagogy, and Purpose - Doud, Tim; Charlton, Zoë (punctum books, 2021)
Broad in scope, Out of Place: Artists, Pedagogy, and Purpose presents an overview of the different paths taken by artists and artist collectives as they navigate their way from formative experiences into pedagogy. Focusing on the realms in- and outside the academy (the places and persons involved in post-secondary education) and the multiple forms and functions of pedagogy (practices of learning and instruction), the contributions in this volume engage individual and collective artistic practices as they adapt to meet the factors and historical conditions of the people and communities they serve through solidarity, equity, and creativity. With this critically, historicist approach in mind, the contributions in Out of Place historicize, study, critique, revise, reframe, and question the academy, its operations and exclusions. The extensive range of contributions, emphasizing community-oriented projects both inside and outside the United States, is grouped into three overarching categories: artists who work in academic institutions but whose social and pedagogical engagement extends beyond the walls of the academy; artists who engage in pedagogical initiatives or forms of institutional critique that were established outside of an art school or university setting; and artist-scholars who are doing transformative and inter/transdisciplinary work within their respective institutions. Collectives and projects represented in Out of Place comprise Art Practical, Axis Lab, BFAMFAPhD, Beta-Local, Black Lunch Table Project, The Black School, The Center for Undisciplined Research, Devening Projects, ds4si, Elsewhere, Ghana ThinkTank, Gudskul, The Icebox Project Space, Las Hermanas Iglesias, The Laundromat Project, Occupy Museums, Peebls, PlantBot Genetics, Queer Conversations on Culture and the Arts, Related Tactics, Side by Side, 'sindikit, Sustainable Native Communities Collaborative, and Tiger Strikes Asteriod.